THE USE OF CRYPTOCURRENCY IN INDONESIA ACCORDING TO ISLAMIC LAW - Muchlis Bahar (International Journal of Artificial Intelligence Research, 2022)
Cryptocurrencies have various functions in the form of tools for making payments, investing, or trading. There are many different types of cryptocurrencies, one of which is Bitcoin. Although it has many functions, its legality in Indonesia is still not legalized and has many pros and cons. The research then aims to analyze the view of Islamic law on the use of cryptocurrency. This research will use a qualitative approach with a library research method that uses data from various previous studies and studies still relevant to this research. This study found that there was still no agreement on the pros and cons of using cryptocurrencies in society. Meanwhile, in Islamic law, cryptocurrency is not issued by a legal/official financial authority, it has not been accepted by the wider community, if because it contains speculation, dharar, gambling, it is already in the abstract, only after that, because there is no physical form it is possible to have gharar and maysir elements. According to Islamic Law and the Indonesian Ulema Council opinion, both as a medium of exchange for payment and as an investment are both unlawful (haram).Â